2016
DOI: 10.2527/jas.2016-0320
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous maternal L-arginine administration to twin-bearing ewes, during late pregnancy, is associated with increased fetal muscle mTOR abundance and postnatal growth in twin female lambs1

Abstract: The aims of this study were to determine whether parenteral Arg administered to well-fed twin-bearing ewes from 100 to 140 d of pregnancy influences fetal skeletal muscle growth, the abundance and activation of mechanistic target of rapamycin (mTOR) protein, and postnatal muscle growth of the offspring. Ewes fed 100% of NRC-recommended nutrient requirements for twin-bearing ewes were administered an intravenous bolus of either 345 μmol Arg HCl/kg BW or saline solution (Control) 3 times per day. At 140 d of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Because lambs were euthanized at day 54 of age, we were not able to follow offspring growth long term. Sales et al (2016) found that female lambs from dams given intravenous boluses of arginine (345-µmol Arg HCl/kg BW 3 times daily) from days 100 to 140 of pregnancy were heavier at day 153 of age and tended to have heavier psoas major muscles than female lambs from dams not administered arginine boluses. Although we saw offspring from all treatments equal by day 40, future studies could follow growth more long term to evaluate the effects of oral administration of arginine at market weight.…”
Section: Lamb Birth Weight and Performancementioning
confidence: 94%
“…Because lambs were euthanized at day 54 of age, we were not able to follow offspring growth long term. Sales et al (2016) found that female lambs from dams given intravenous boluses of arginine (345-µmol Arg HCl/kg BW 3 times daily) from days 100 to 140 of pregnancy were heavier at day 153 of age and tended to have heavier psoas major muscles than female lambs from dams not administered arginine boluses. Although we saw offspring from all treatments equal by day 40, future studies could follow growth more long term to evaluate the effects of oral administration of arginine at market weight.…”
Section: Lamb Birth Weight and Performancementioning
confidence: 94%
“…Sterndale et al (19) noted that there was no significant difference between selenium vitamin E and control in glucose level in ewes during pregnancy (33). Yunta et al (31) noted that giving arginine during pregnancy did not significantly affect glucose (12,16,21,26). While the results of the current study with Jarad and Al-Kaisei (34) showed that the Arginine had an effective effect in reducing the blood glucose level .…”
Section: -Blood Glucose (Table -7)mentioning
confidence: 47%
“…Recent studies have shown that arginine plays a role in stimulating the growth and development of the placenta (9), Prolactin and IGF Insulin like Growth Factor 1, IFN-t, Glycogen (10). Treatment of pregnant ewes with arginine or selenium plus vitamin E increases fetal growth by increasing The arrival of food to the fetus and the maintenance of pregnancy (11), nitrogen uptake and reduction of ammonia toxicity in tissues (12). However the previous studies did not showed significantly the use of arginine with selenium and vitamin E during pregnancy and its impact on the state of health of the dam and fetus and may considered as an indicators of the values of lambs and chemists in addition to measuring concentrations of sex hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Pacheco et al (2016) reported that proportions of arginine, citrulline and ornithine in plasma of lactating cows fed fodder beet were lower than those from cows fed ryegrass, suggesting the possibility of insufficient AA supply/synthesis. Arginine, in particular, has been found to have a key role in foetal growth and development (McCoard et al 2016), where parenteral supplementation to twin-bearing pregnant sheep in the last trimester increased foetal brown-fat reserves and core body temperature at birth (McCoard et al 2014), increased female lamb birth weight (McCoard et al 2013), placental development and function (van der Linden et al 2015) and improved offspring postnatal growth rate and muscle mass (Sales et al 2016). The potential for changes in specific AA to mediate, at least in part, the differences in ewe and lamb performance observed in this study warrant further investigation.…”
Section: Parturition Parturition Parturition Parturition Parturition mentioning
confidence: 99%